Analisa Antimagicness Super dari Shackle Graf Parasut dan Aplikasinya pada Polyalphabetic Cipher - Riza Nurfadila; Ika Hesti Agustin; Kusbudiono Kusbudiono (jcgant, 2021)
Super (a,d)-H-antimagic total covering on a graph G=(V,E) is the total labeling of λ of V(G) E(G) with positive integers {1, 2, 3,… ,|V(G) E(G)|}, for any subgraph H' of G that is isomorphic to H where H' = _v V(H) λ (v ) + _e E(H) λ (e) is an arithmetic sequence {a, a+d, a+2d,…,a+(s-1)d} where a, d are positive numbers where a is the first term, d is the difference, and s is the number of covers. If λ(v)_v V = 1,2,3,…,|V(G)| then the graph G have the label of super H-antimagic covering. One of the techniques that can be applied to get the super antimagic total covering on the graph is the partition technique. Graph applications that can be developed for super antimagic total covering are ciphertext and streamcipher. Ciphertext is an encrypted message and is related to cryptography. Stream cipher is an extension of Ciphertext. This article study the super (a,d)-H-antimagic total covering on the shackle of parachute graph and its application in ciphertext. The graphs that used in this article are some parachute graphs denoted by shack(P_m,e,n).